Taxonomy, ecology, and geographical distribution of the species of the genus Thermocyclops Kiefer, 1927 (Copepoda, Cyclopoida) in São Paulo State, Brazil, with description of a new species - W. M. Silva (Brazilian Journal of Biology)
The taxonomy and ecology of the cyclopoid copepod genus Thermocyclops were studied. Samples were collected in 207 water bodies located in the 22 hydrographic basins of São Paulo State, Brazil, including large reservoirs, small and shallow lakes, and ponds and rivers. The genus Thermocyclops inhabits mainly water bodies within a limnetic region. Four species were found, of which one is new: Thermocyclops iguapensis, which occurred in the reservoirs of the Ribeira do Iguape and Paraíba do Sul basins. The description of the new species and the geographical distribution of all four species in São Paulo State are presented. Thermocyclops decipiens was the most frequent species, occurring in 71% of the water bodies within a limnetic region. This species is characteristic of eutrophic environments where it can occur in great abundance, whereas Thermocyclops minutus is characteristic in oligotrophic systems. Thermocyclops inversus and Thermocyclops iguapensis n. sp. were not common but can occur together with Thermocyclops decipiens.